Does central bank independence contribute to fiscal prudence in EU countries? - Petkovski, Mihail; Stojkov, Aleksandar; Jordan, Kjosevski (Panoeconomicus, 2024)
This study explores the influence of central bank independence (CBI) on fiscal deficits in 27 European Union (EU) member states from 1990 to 2023. Utilizing system generalized method of moments, we find that countries with more independent central banks tend to exhibit stronger fiscal balances. However, the impact is tempered within the Eurozone. Positive coefficients for GDP growth, adherence to fiscal rules, and democratic governance structures highlight their importance for fiscal sustainability. Our findings underscore the complex interplay of factors shaping fiscal balances, emphasizing the need for policy coordination and prudent fiscal management within the EU.